Dysembryoplastic Neuroepithelial Tumor: A Rare Brain Tumor with Excellent Seizure Control after Surgical Resection - Arora, Rajnish Kumar; Bhargava, Pranshu; Arora, Poonam; Joshi, Prashant; Basu, Garga; Mittal, Radhey Shyam (Indian Journal of Neurosurgery, 2020)
Introduction Dysembryoplastic neuroepithelial tumor (DNET) is a rare cause of intractable epilepsy, which has excellent results in terms of seizure control after surgical resection. We present one such case, because of its rarity, to highlight the effect of tumor removal on seizure control, particularly DNET.Materials and Methods/Case Summary A 9-year-old male patient presented with sudden onset of partial seizures for the past 6 months. There were five episodes. In each episode, the patient engaged in irrelevant talk, followed by deviation of mouth to left and twitching movements. The episode lasted 5 minutes and there was no loss of consciousness. There was no aura or tongue bite, and in one of the episodes, the patient lost consciousness. There was no other significant positive history. On examination, the child was consciously alert, without focal neurological deficit or features of meningitis. There was no papilledema. The patient was on phenytoin sodium, phenobarbitone and clobazam. Magnetic resonance imaging (MRI) of brain was done with and without contrast. MRI revealed a lesion approximately 4.1 × 3.6 × 3.2 cm in the right medial temporal lobe. It was hypointense to brain on T1 and fluid-attenuated inversion recovery (FLAIR), and hyperintense on T2-weighted images. Diffusion restriction was present and there was minimal contrast uptake. There was no evidence of mass effect or midline shift After discussing the risks and benefits with parents, the patient underwent preanesthetic checkup, and was taken up for craniotomy and excision of tumor. Gross total excision was done. The child was started orally on day 1 postoperatively and ambulated. There were no further seizure episodes. The patient was continued on phenytoin and clobazam, and phenobarbitone was tapered gradually. At 6 months, the child was seizure-free.Conclusions DNET are rare tumors occurring early in life and presenting with intractable seizures. Surgical resection offers a good and safe chance for long-term seizure control.
Keywords: dysembryoplastic; neuroepithelial; seizure